Association Between Dietary Inflammatory Index and Mental Health: A Systematic Review and Dose–Response Meta-Analysis - Chen, Guo-Qiang; Peng, Chun-Ling; Lian, Ying; Wang, Bo-Wen; Chen, Peng-Yu; Wang, Gang-Pu (Frontiers in Nutrition, 2021)
Objective: We aimed to systematically evaluate the association between dietary inflammatory index (DII) and mental health. Methods: We searched the PubMed, Embase, and Web of Science from their inception to Dec. 31, 2020. Categorical meta-analysis and dose-response meta-analysis were performed to evaluate association between DII and mental health. Results: A total of 16 studies were included in this meta-analysis. Compared with the lowest DII category, the highest category was significantly associated with a variety of mental health outcomes, with the following pooled odd ratios (ORs) and 95% conﬁdence intervals (95% CIs): 1.28 (1.17-1.39) for symptoms of depression, 1.27 (1.08-1.49) for symptoms of anxiety, 1.85 (1.43-2.40) for distress, and 4.27 (1.27-14.35) for schizophrenia. Furthermore, there was a linear dose-response relationship between DII and symptoms of depression in that a 1-unit increment in DII was associated with an increased risk of 6% for symptoms of depression (OR: 1.06, 95% CI: 1.03-1.19). Conclusion: The present study indicates that more pro-inflammatory diet, as estimated by the higher DII score, is associated with symptoms of mental disorder. It may be of clinical and public health significance regarding the development of novel nutritional psychiatry approaches to promote good mental health.